Circulating heat shock protein 27 as a novel marker of subclinical atherosclerosis in type 2 diabetes: a cross-sectional community-based study - Wang, Xinru (BMC Cardiovasc Disord, 2020)
BACKGROUND: Heat shock protein 27 (HSP27) has been proposed as a vital protective factor in atherosclerosis. The objective of the present study was to evaluate the association between circulating HSP27 and carotid intima–media thickness (IMT) in individuals with type 2 diabetes and to determine whether HSP27 represents an independent marker of subclinical atherosclerosis in this patient population. METHODS: We performed a cross-sectional community-based study in 186 Chinese subjects with a median duration of type 2 diabetes of 8.2 years who underwent ultrasound carotid IMT measurement. Serum HSP27 levels were assessed by ELISA. RESULTS: Serum HSP27 levels were significantly higher in the IMT (+, > 1.0 mm) group than in the IMT (−, ≤1.0 mm) group, with the median values of 8.80 ng/mL (5.62–12.25) and 6.93 ng/mL (4.23–9.60), respectively (P = 0.006). The discriminative value of HSP27 to evaluate IMT was 7.16 ng/mL and the area under the curve was 0.72 (95%CI = 0.64–0.80, P = 0.0065). Spearman’s rank correlation analysis demonstrated that the concentrations of circulating HSP27 were positively associated with carotid IMT (r = 0.198, P = 0.007) and blood urea nitrogen (r = 0.170, P < 0.05). Furthermore, in the logistic model, serum HSP27 levels were found to be independent predictors for carotid IMT in type 2 diabetic patients after adjustment for onset age of diabetes, blood pressure, total cholesterol and C-reactive protein (OR = 1.085, P = 0.022). CONCLUSIONS: Circulating HSP27, positively correlates with carotid IMT, is an independent predictor for early atherosclerotic changes in diabetes, and may represent a novel marker of subclinical atherosclerosis in type 2 diabetes.